Changes in the physiological and numerical components of canola yield in the face of reductions in incident solar radiation - García Hernández, Gustavo; Araujo Díaz, Rogelio; Estrada Campuzano, Gaspar; Martinez Rueda, Carlos Gustavo; Domínguez López, Aurelio; Villanueva Carvajal, Adriana (Revista Mexicana de Ciencias Agrícolas, 2020)
In this work, the period of time in which canola yield is most sensitive to changes in resource availability was identified, and the physiological and numerical components that are most affected by reductions in incident radiation at different times of the cycle were identified. cultivation. Two anola spring genotypes were planted, one short-cycle and one intermediate-cycle, which were subjected to 10-day shading treatments (14 in total) during the winter 2015 and spring 2016 agricultural cycle. The treatments (cultivar combination and shading moments) were established in an arrangement of divided plots, where the main plot was assigned to the cultivars, while the shading moments were assigned to the subplots, the latter were distributed in a randomized complete block design with three repetitions. The most significant reductions in grain yield (33%) due to the effect of shading for Bioaureo 2486 were observed from 140 °Cd up to 410 °Cd after the start of flowering, with a total of 550 °Cd. In Hyola 61 this time window presented from -45 °Cd up to 250 °Cd with a total of 295 °Cd, with a decrease in yield of up to 40%. The numerical component of yield most affected by reductions in incident radiation levels was the number of grains. On the other hand, the number of grains per pod and the number of pods per unit area largely explained the changes in the number of grains. These results will allow better orientation of the genetic improvement and agronomic management strategies tending to increase the potential yield in this crop.
Keywords: Brassica napus L.; incident radiation; number of grains; yield